2007
DOI: 10.1083/jcb.200701030
|View full text |Cite
|
Sign up to set email alerts
|

Eps15 and Dap160 control synaptic vesicle membrane retrieval and synapse development

Abstract: Epidermal growth factor receptor pathway substrate clone 15 (Eps15) is a protein implicated in endocytosis, endosomal protein sorting, and cytoskeletal organization. Its role is, however, still unclear, because of reasons including limitations of dominant-negative experiments and apparent redundancy with other endocytic proteins. We generated Drosophila eps15-null mutants and show that Eps15 is required for proper synaptic bouton development and normal levels of synaptic vesicle (SV) endocytosis. Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 87 publications
10
148
2
Order By: Relevance
“…refs. [26][27][28][29][30][31]. First, synaptic vesicle size was increased in both mutants with respect to WT ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…refs. [26][27][28][29][30][31]. First, synaptic vesicle size was increased in both mutants with respect to WT ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1B). In contrast to the essential roles of the FCHO proteins, Eps15, and intersectin in other species (7,8,25), null mutations in each gene failed to substantially impact C. elegans viability or embryonic development (Table S1). …”
Section: The Fei Adaptor Complex Regulates Protein Sorting In the Endmentioning
confidence: 99%
“…Within the periactive zone, exocytosed synaptic vesicle proteins are translocated and then recaptured by endocytic sorting adaptors, including stonin 2 (also known as stoned B) and perhaps AP180. It is likely that these adaptor proteins in turn are spatiotemporally organized by large multidomain scaffolds such as intersectin and EPS15 (REFS 62,72). The periactive zone also contains cytoskeletal elements, in particular actin and perhaps septin filaments.…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…Genetic studies have identified the multidomain endocytic scaffolding proteins intersectin [60][61][62]71 and epidermal growth factor receptor substrate 15 (EPS15) 72 as crucial for synaptic vesicle membrane retrieval and synapse development in Drosophila melanogaster and Caenorhabditis elegans. Expression levels of intersectin and EPS15 are interdependent, and the phenotypes observed on loss of either protein are nearly identical, indicating a close functional relationship between both proteins 72 . Consistent with these observations EPS15 and intersectin, together with FCHo proteins, serve as nucleators for clathrin-coated pit assembly 73 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%